2020
DOI: 10.1007/s40820-020-00478-2
|View full text |Cite
|
Sign up to set email alerts
|

Highly Thermo-Conductive Three-Dimensional Graphene Aqueous Medium

Abstract: Highly thermo-conductive aqueous medium is a crucial premise to demonstrate high-performance thermal-related applications. Graphene has the diamond comparable thermal conductivity, while the intrinsic two-dimensional reality will result in strong anisotropic thermal conductivity and wrinkles or even crumples that significantly sacrifices its inherent properties in practical applications. One strategy to overcome this is to use three-dimensional (3D) architecture of graphene. Herein, 3D graphene structure with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Therefore, many techniques are used to interfere with the growth of the boundary layer and enhance the cooling performance of the heat sink (Liu et al, 2022;Tian et al, 2022). Nanofluids, like threedimensional graphene nanofluid, were used as coolant media to change the fluid physical parameters, which was widely used in the cooling process of chips (Bo et al, 2020). In addition, changing the geometry, using vortex generation structure, and performing flow disruption are very effective ways (Zheng et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many techniques are used to interfere with the growth of the boundary layer and enhance the cooling performance of the heat sink (Liu et al, 2022;Tian et al, 2022). Nanofluids, like threedimensional graphene nanofluid, were used as coolant media to change the fluid physical parameters, which was widely used in the cooling process of chips (Bo et al, 2020). In addition, changing the geometry, using vortex generation structure, and performing flow disruption are very effective ways (Zheng et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the power systems for conventional cooling technologies are supplied mainly by fossil fuel‐based thermal power plants, which are the main source of anthropogenic carbon emissions. Consequently, developing high‐efficiency, environmentally friendly, and sustainable cooling strategies have become attractive for improving the working efficiency of buildings, data centers, and photovoltaics (PVs), and reducing carbon emissions, while meeting ever‐increasing energy demands 15,17–19 …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, developing highefficiency, environmentally friendly, and sustainable cooling strategies have become attractive for improving the working efficiency of buildings, data centers, and photovoltaics (PVs), and reducing carbon emissions, while meeting ever-increasing energy demands. 15,[17][18][19] Evaporative cooling based on the liquid-vapor phase change of water 20,21 is a promising alternative to air conditioners owing to its super high enthalpy, that is, ~2450 J/g. For example, a technique used worldwide to cool high-temperature roads is spraying water for surface cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to graphene powders, graphene foams (GFs) have higher conductivity [ 25 , 26 , 27 ], more uniform distribution, and higher porosity [ 28 ]. However, seldom have studies been reported on electro-activated SMPs embedding chemical vapor-deposited graphene foams (CVD-GFs).…”
Section: Introductionmentioning
confidence: 99%